2019
DOI: 10.1038/s41598-019-52192-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of indoleamine 2,3-dioxygenase in testicular immune-privilege

Abstract: Male meiotic germ cell including the spermatozoa represent a great challenge to the immune system, as they appear long after the establishment of normal immune tolerance mechanisms. The capacity of the testes to tolerate autoantigenic germ cells as well as survival of allogeneic organ engrafted in the testicular interstitium have led to consider the testis an immunologically privileged site. Disruption of this immune privilege following trauma, tumor, or autoimmune orchitis often results in male infertility. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Indoleamine-2,3-dioxygenase (IDO) expression in porcine Sertoli cells and the ability of these cells to restore immune tolerance in NOD mice ( 42 ) point to a role of IDO in testis immune privilege. Current findings from functional in vivo experimental studies confirm that tryptophan metabolism modulates inflammatory immune response to spermatic antigens ( 43 ).…”
Section: Immune Privilege Of the Testismentioning
confidence: 80%
“…Indoleamine-2,3-dioxygenase (IDO) expression in porcine Sertoli cells and the ability of these cells to restore immune tolerance in NOD mice ( 42 ) point to a role of IDO in testis immune privilege. Current findings from functional in vivo experimental studies confirm that tryptophan metabolism modulates inflammatory immune response to spermatic antigens ( 43 ).…”
Section: Immune Privilege Of the Testismentioning
confidence: 80%
“…Fallarino et al found that SCs can produce indoleamine 2, 3-dioxygenase (IDO), TGF-β, and complementary inhibitors, and they are an important inducer of inflammation and the subsequent immune response, when they are used as isolated SCs to treat experimental type 1 diabetes [112]. The most recent data further prove the immune regulatory role of IDO in EAO rats [116]. Microarray analyses and qRT-PCR in SCs demonstrate that SCs express serine protease inhibitor (SERPIN)G1, which targets the initial step of the complementary cascade activation, thus preventing further amplification [117].…”
Section: T Lymphocytes and Sertoli Cellsmentioning
confidence: 98%
“…IDO is reported to induce DCs to initiate immune tolerance and to stimulate the development of Tregs in tumors and pregnant uterus both are immunologically privileged site like testes (117)(118)(119). Recently, the IDO-based mechanism has also been identified to be involved in testicular immune privilege (120). The expression of IDO is rapidly increased when DCs suffer from LPS/IFN-g-stimulation, leading to limited microbial growth and reduced injurious hyperinflammatory responses (121,122).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…The expression of IDO is rapidly increased when DCs suffer from LPS/IFN-γ-stimulation, leading to limited microbial growth and reduced injurious hyperinflammatory responses ( 121 , 122 ). However, testicular DCs mildly expressed IDO, meanwhile IDO activity is reduced in EAO rat ( 120 , 123 ). These differences might be attributed to the fact that the Sertoli cells indirectly inhibit LPS-induced DCs maturation through paracrine effect.…”
Section: Possible Contribution Of Metabolism Of Immune Cells To Male Reproductionmentioning
confidence: 99%